Late Onset Prosthetic Hip Joint Infection in Two Patients of Rheumatoid Arthritis Treated With Etanercept - Hayashi SHINYA; Sakai YOSHITADA; Fujishiro TAKAAKI; Hashimoto SHINGO; Kanzaki NORIYUKI; Kuroda RYOSUKE; Kurosaka MASAHIRO (Archives of Rheumatology, 2015)
In this article, we report two rheumatoid arthritis (RA) patients who developed rare, late onset infection after total hip arthroplasty (THA) following etanercept therapy. First patient was a 74-year-old female with RA. Treatment with etanercept was initiated three years after THA, and infection involving THA was observed two months after the initiation of etanercept. Patient was successfully treated by open debridement. Second patient was a 62-year-old female with RA. THA was performed, and infection involving THA was observed four years after the initiation of etanercept. This patient was also successfully treated by open debridement. However, when etanercept was reinitiated two years after open debridement, infection reoccurred. Immediately, open debridement was performed, prosthesis was removed, and antibiotic-impregnated, cement spacer was inserted. THA was repeated two months after open debridement. Late onset infection developing after THA following etanercept therapy in RA indicates that tumor necrosis factor-alpha blockers should be carefully administered in patients who have undergone THA.